PENDIDIKAN DALAM PERSPEKTIF KRITIS-EMANSIPATORIS (Telaah terhadap Kurikulum dan Metode Pembelajaran) - Yumidiana Tya Nugraheni; Agus Firmansyah (MAMBA'UL 'ULUM, 2020)
The modern era is a time of development of the positivism philosophy. Modern world life is based on the paradigm of positivism thinking. The paradigm of positivism thinking believes that all science is mathematical which is characterized by objective, measurable, scientific, rational and universal thinking patterns. These four ways of thinking have brought modern civilization to the triumph of science. On the other side, a civilization based on the modern paradigm experiences various kinds of humanitarian problems. The paradigm of modern thinking is not suitable when it is associated with social problems including the education. Jurgen habermas, a Frankfurt school figure, offers solutions to overcome social problems that cannot be overcome by modern paradigms. Habermas developed a critical theory that had been put forward by the previous generation of Frankfrut figures. The theory he offered was a critical theory of emancipation and a theory of communicative action. Emancipatory critical theory and communicative action theory are able to answer problems in the world of education that cannot be answered by the positivistic thinking paradigm.